Effects of Water Invasion to Design and Production Procedure in Fractured Basement Reservoir, SuTu Den oil Field and Prevention Solutions - Xuân, Trần Văn (VNU Journal of Science: Earth and Environmental Sciences; Vol 31 No 1, 2015)
During oil and gas production processes, especially in fractured basement reservoir those related to formation water, the ability of water invasion is quite possible. Based on realistic production and injection activities at SuTuDen oil field, CuuLong Basin, Vietnam, the author researched, evaluated the effects of formation water to oil and gas bearing fractured basement reservoir which each exploration, appraisal, development and production stage accordingly, determined the solution, appropriate technology to attain the targets. In exploration stage, early detected the connate water appearance would guide to discover the petroleum accumulation or avoid drill the dry holes, determine the initial oil water contact which serving for appraisal well design as well could be the foundation to estimate the hydrocarbon initial in place. In development, production stages, in the case particularly methods applied, such as well observing, reservoir monitoring, formation testing, production technology diagram updating and revising, water invasion possibility, level predicting to reservoir, since then build up the theories in order to propose the instant solutions (reducing flow rate, adjusting production –water injection regime, isolating potential water influx) as well as long term solutions (monitoring pressure behavior of production well closely, optimizing production-injection design, determining and quantifying the origins of production water) to prevent and protect water invasion hence increasing oil recovery efficiency. Keywords : Fractured basement reservoir, formation water, production and injection, MPLT, DST, hydrodynamic model, BS & W, EOR.